Heterosis and inbreeding depression for yield and its components traits in barley (Hordeum vulgare) - RAIKWAR, R S (The Indian Journal of Agricultural Sciences, 2020)
Heterosis and inbreeding depression was analysed using a set of diallel crosses involving 10 diverse parents (excluding reciprocals). Heterosis over standard parent for grain yield per plant ranged from -9.65–45.45 (%) and -14.78–12.05 (%) under normal and late sown conditions, respectively and heterosis over better-parent for grain yield per plant ranged from -26.43–70.77(%) and -32.16–12.05(%) respectively. Nature and magnitude of heterosis and inbreeding depression varied across crosses, characters as well as environments. Considering the very high degree of heterosis in desirable direction, the importance of non-additive components of genetic variance was observed for yield and most of the yield contributing components. Cross II (K 603 × Azad) and cross IV (RD 2618 × PL 708) revealed better specific cross combinations to be used for heterosis. The study revealed good scope for commercial exploitation of heterosis as well as isolation of pure lines among the progenies of heterotic F1 for improvement of yield levels in barley.